MODEL PENERAPAN PENDIDIKAN KEBENCANAAN PADA DINAS PENDIDIKAN KABUPATEN PIDIE TERHADAP BANJIR DIKECAMATAN TANGSE - Fahrizal Fahrizal; Muhammad Zaini (Jurnal Sains Riset, 2022)
Floods and landslides are the most frequent disasters in Indonesia, especially in Pidie District, Tangse District in 2017-2021 and have an impact on 25,214 people who inhabit 28 villages. Data for the last 4 years shows that there are 3 schools affected by floods and landslides, but until this research was conducted there was no accurate data on the number of affected education offices. Problem Formulation 1. What is the model for implementing disaster education during the flood disaster in Tangse District 2. What actions have been taken by the Pidie District Education Office. (2) To find out what actions were taken by the Pidie District Education Office. This study uses a qualitative research approach. The qualitative method is part of the research procedure that produces descriptive data in the form of written or spoken words from people and observed behavior. The results of this study are teachers have tried to provide disaster education in their own way but still have not utilized the environment and the potential of its natural resources; Disaster education that has been implemented has not been clearly integrated with the learning curriculum; Coordination of flood disaster management with local agencies has been carried out but is not yet optimal. So it can be said that a more comprehensive and sustainable effort is needed to help prepare junior high school teachers to realize a culture of alertness, safety culture and a culture of disaster risk reduction in junior high schools.Keywords: Model, Implementation, Education, Disaster